Етнокультурна своєрідність Волині - Давидюк, В. (Народна творчість та етнографія, 2005)
Regional distinguishing features like as material values, spiritual and socio-standards of Volyn inhabitants' culture are considered in this article. Taking as a basis a series of archaeological sources and own field research materials an author proved an ancient of a settlement in Volyn region and that it's population was rooted in this territories for ages. One can find a detail analysis of a number of peculiarity rites, that take there place till present-day among the inhabitants of Volyn.